Expense savings through technology acceptance: Analysis of the adoption of electronic systems in public institutions (Research, Society and Development, 2021)
This study seeks to analyze the cost savings in public institutions through the Acceptance and Use of technology in the computerization of electronic processes. In this sense, the Theory of Acceptance and Use of Technology (UTAUT) is used to explain adherence to a procedural system of electronic processing, which replaces paper and other office supplies to improve performance resulting from resource savings. It is an exploratory, descriptive and explanatory research as to the objective, carried out through document analysis with a quantitative approach. To achieve the proposed objective, expenses were raised before and after the implementation of the computerized electronic system in 94 federal executive branches, between 2011 and 2020. Based on the construction of two research hypotheses, the analyzes used the test of Wilcoxon to verify the difference in the execution of expenses with the system implement, but also Factor Analysis combined with the Kruskall-Wallis test to identify a possible systemic behavior change in costs arising from the use of electronic systems. The results show that the adoption of the system alone may not provide sufficient arguments for adherence to the technology. However, based on the theoretical component, the arguments of agility, ease of use and information security are relevant in government action for the decision-making process of managers.